The Effect Of Minimum Wages And MSMEs On Economics Growth In Tulungagung - Amalia Azizah; Lucky Rachmawati (Universitas Negeri Surabaya, 2022)
The stability of the region can be shown in the economic growth. One's income can be used to examine welfare. MSMEs and the minimum wage are two sources of personal income. The goal of this study is to ascertain how Tulungagung's economic growth is impacted by the minimum wage and the number of umkm. Secondary data were used in this study, and literature studies were conducted to get them. The used data spans the years 2011 through 2021. Multiple linear regression is the analytical technique utilized to ascertain the impact of the minimum wage and the proportion of MSMEs on Tulngagung's economic growth. According to the study's findings, the number of MSMEs has an impact on Tulungagung's economic growth whereas the minimum wage has no bearing on it. The minimum wage and the proportion of MSMEs, meanwhile, have an impact on Tulungagung's economic expansion.